Selection Criteria for Improving Yield in Chili (Capsicum annuum) - S. Chakrabarty; A. K. M. Aminul Islam (Advances in Agriculture)
The present investigation was carried out to estimate the genetic variability and character association. Significant differences were observed among the genotypes for all the 15 traits for 20 chili genotypes. The highest genotypic coefficient of variation and phenotypic coefficient of variation were found for ten edible fruit weight, number of fruits per plant, fruit yield per plant, ten dry fruit weight, fruit length, fruit width, and weight of seeds per fruit. High heritability coupled with very high genetic advance as per cent of mean was observed for ten edible fruit weight, ten dry fruit weight, fruit length, number of fruits per plant, and fruit yield per plant. Phenotypic correlation coefficient among different traits indicated that fruit yield per plant at green stage had significant and positive association with ten edible green fruit weight, number of primary branches, harvest duration, and first fruit maturity and significant negative correlation with days to first picking. The path coefficient analysis revealed that days to first picking had the maximum positive direct effect on fruit yield per plant followed by harvest duration, ten edible fruit weight, ten dry fruit weight, hundred-seed weight, number of fruits per plant, first fruit maturity, and number of primary branches. Days to first picking had the maximum positive direct effect but significant negative effect with fruit yield per plant which indicated that the trait should be selected to expunge the undesirable indirect effect in order to make use of the direct effect. Therefore, selection should be practiced for ten edible fruit weight, ten dry fruit weight, number of fruits per plant, harvest duration, and hundred-seed weight for direct improvement of fruit yield per plant.